Neonatal effects of maternal magnesium sulphate in preeclampsia: a case control study - Sengottaian, Karunaa Joe; Rangappa, Sheela Shivamonga (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Preeclampsia is a significant public health problem in developed and developing countries. It is a multi-organ system disorder, hence making it demanding to find out severity markers.4 Awareness, recognition and knowledge of risk factors of preeclampsia will assist in predicting and lessen the recurrence of preeclampsia. In severe cases of preeclampsia and in eclampsia, magnesium sulfate is an effective anticonvulsant.Aims and objectives were: to document the clinical parameters of patients with or more than 28-week gestation having preeclampsia or eclampsia receiving magnesium sulphate and patients with or more than 28-week gestation having preeclampsia but not receiving magnesium sulphate; and to compare and study the obstetric and neonatal outcomes between the groups. Methods: A case control study was performed among patients who delivered at RLJH hospital during study period (July 2020-July 2021), subjects who were administered magnesium sulphate due to maternal conditions were taken as cases and the subjects who did not receive magnesium sulphate were taken as controls. Obstetrical and neonatal outcomes were compared between both the groups. Data was entered in Microsoft excel sheet. Unpaired t test was performed. P value less than 0.0001 was considered significant. Results: Magnesium sulphate did not have significant effects on the neonatal and obstetrical outcome. Conclusions: The association between magnesium sulphate administration and neonatal outcomes were studied and it concludes that the administration of magnesium sulphate for the mother didn’t have significant effects on the neonatal and obstetrical outcome.